A lysosomal probe for monitoring of pH in living cells and ovarian tumour. (April 2017) - Li, Bo; Ge, Guang bo; Wen, Lanlan; Yuan, Ye; Zhang, Ran; Peng, Xiaojun; Liu, Fengyu; Sun, Shiguo
Abstract: Intracellular pH is important in regulating various cellular behaviour and pathological conditions. We synthesised a rhodamine-based lysosomal pH probe (hereafter referred to as RD) with a pKa of 4.10. The probe exhibited favourable "on-off" reversibility between pH 3.25 and 7.20 for at least five cycles. RD can be employed to distinguish cancer cells from normal cells on the basis of different fluorescence response. RD performed well in the detection of lysosomal pH induced by artesunate, chloroquine and dexamethasone in MCF-7 cells. The intense fluorescence of RD in ovarian tumour indicated the higher acidity in tumour tissues than that in normal tissues. Furthermore, RD worked well in the imaging of excised mouse stomach and living mice under acidic stimulation. These data demonstrate the applicability of RD in monitoring pH in complex biological systems. Highlights: Probe RD can be employed to distinguish cancer cells from normal cells on the basis of fluorescence response. Performing well in the detection of lysosomal pH induced by artesunate, chloroquine and dexamethasone in cells. Distinguishing tumour tissues from normal tissues by intense fluorescence of RD in ovarian tumour. Working well in the imaging of ovarian tumour, excised mouse stomach and living mice under acidic stimulation.